The Identification of Green Spaces in UTHM Parit Raja Campus - Mahadhir, Muhammad Nuriskandar; Muhazim, Muhamad Faris Hamzi; Mohd Mubarak, Nur 'Insyiraah; Ngadiman, Nor Hayati (Multidisciplinary Applied Research and Innovation, 2023)
Most of the higher education campuses have green space, which is beneficial to campus life. Even though various evaluations have examined the relationship between nature and student’s health, there is still a need for studying correlation between student’s perception towards green space. Since currently there is no research that has been made related to the green space, this study aims to identify the green space location in UTHM Parit Raja campus and to measure student perception of green space on UTHM Parit Raja campus. An orthophoto map of UTHM Parit Raja is analyzed by Global Mapper software which is used to identify location and measure the green space. Other that that, a survey of student perception of green space in UTHM Parit Raja campus is conducted. The survey is to measure the appreciation of green space on accessibility, cleanliness, facilities, and attraction. The respondents are those who are currently pursuing students at the UTHM Parit Raja Campus. Microsoft Excel software is used for data analysis with the collection, organisation, and systematic examination of data. The significance of this study is to make room for improvement regarding how to make use of green space to the max potential in the future as well to ensure the green space area percentage is in accordance with the existing standards. The summarize the findings, the total area of green space in UTHM Parit Raja campus required by the institutional setting is successfully achieved with a percentage of 63.74% land covered in green space. Furthermore, the feedback from the survey of student’s perception is evaluated as the green space reflects the students’ perception. Therefore, this study is successful since it able to prove the relation between both of the objectives.